Democratic Citizenship and Digital Literacy - Permpoonwiwat, Supanat; Mansap, Saranyu; Kaewmano, Jaruwan (King Prajadhipok’s Institute Journal, 2022)
The objectives of this research were 1) to study the digital literacy of Thai people in democratic regime, 2) to study the correlation between Thai democratic citizenship and digital literacy, and 3) to study the ways to promote digital literacy among Thai democratic citizens. The research method consisted of a survey of opinions by means of questionnaires from a sample of 400 people, and qualitative data were collected through group discussion and interviews with 13 experts. The statistics used in the data analysis were percentage, mean score, and standard deviation. Opinion and behavior were compared with f-test (ANOVA) and correlation analysis was done between democratic citizens and digital literacy using Pearson Product Moment Correlation Coefficient (r). The results showed that sample group had a high level of democratic citizenship ( = 3.28), with a high level of democratic values ( = 3.39), and sometime-demonstrated democratic values ​​( = 2.45). The sample group had a high level of digital literacy ( = 2.61), with a high level of digital proficiency ( = 2.89), and sometime demonstrated digital literacy behavior ( = 2.45) Democratic citizenship was positively correlated with digital literacy at a medium to high level (r = .455). Awareness of rights is highly correlated to digital literacy, and public participation is correlated to digital literacy. The research recommends that the government should establish a key framework for developing digitally literate democratic citizens at a national level. An authority should be established to collect knowledge, information, and develop tools to promote digital literacy and evaluate digital literacy status, and integrate digital literacy into the teaching and learning process. For agencies working to promote digital literacy, democratic values ​​should be integrated into their work or developed into a curriculum for effective implementation, and there should be research to monitor and assess digital literacy of citizens according to international principles to keep up with changing situations of technology and the digital world.